New Insights in the Immunobiology of IL-1 Family Members - Veerdonk, Frank V.; Netea, Mihai (Frontiers in Immunology, 2013)
The interleukin-1 (IL 1) family of ligands is associated with acute and chronic inflammation, and plays an essential role in the non-specific innate response to infection. The biological properties of IL 1 family ligands are typically pro-inflammatory. The IL 1 family has 11 family members and can be categorized into subfamilies according to the length of their precursor and the length of the propiece for each precursor (Figure 1). The IL 1 subfamily consists of IL 1α, IL 1β, and IL 33, with the longest propieces of the IL 1 family. IL 18 and IL 37 belong to the IL 18 subfamily and contain smaller propieces than IL 1 and IL-33. Since IL 37 binds to the IL 18Rα chain it is part of the IL 18 subfamily, however it remains to be elucidated how the propiece of IL 37 is removed. IL 36α, β, and γ as well as IL 36 Ra belong to the IL 36 subfamily. In addition, IL 38 likely belongs to this family since it has the ability to bind to the IL 36R. The IL 36 subfamily has the shortest propiece. The one member of the IL 1 family that cannot be categorized in these subfamilies is IL 1 receptor antagonist (IL 1Ra), which has a signal peptide and is readily secreted. In the present review we will describe the biological functions of the IL-1F members and new insights in their biology.